Clinical companion for medical-surgical nursing : patient-centered collaborative care - Winkelman, Chris (St. Louis, Missouri : Elsevier Saunders, 2013)
The Clinical Companion for Ignatavicius & Workman: Medical-Surgical Nursing: Patient-Centered Collaborative Care, 7th Edition, is an easy-to-use, A-Z guide to 245 common medical-surgical conditions and their management. Written in a reader-friendly, direct-address style, this handbook is a convenient quick reference that you can carry with you on clinical days. A-Z synopses of 245 diseases and disorders, along with related collaborative care, serve as both a quick reference for clinical days and a study resource for essential information Streamlined.
Part One: Concepts of Medical-Surgical Nursing -- Cancer Pathophysiology -- Overview -- Carcinogenesis/oncogenesis -- Cancer etiology and genetic risk -- Patient-centered collaborative car -- Cancer Treatment Issues -- Cancer surgery -- Overview -- Patient-centered collaborative care -- Radiation therapy -- Overview -- Patient-centered collaborative care -- Chemotherapy -- Overview -- Patient-centered collaborative care -- Hormonal manipulation -- Photodynamic therapy -- Overview. Patient-centered collaborative care Immunotherapy: biological response modifiers -- Overview -- Patient-centered collaborative care -- Targeted therapy -- Oncologic emergencies -- End-of-Life Care -- Overview -- Patient-centered collaborative care -- Assessment -- Interventions -- Inflammation and Immunity -- Overview -- Organization of the immune system -- Inflammation -- Sequence of inflammatory responses -- Consequences of inflammation -- Immunity -- Antibody-mediated immunity -- Acquiring antibody-mediated immunity -- Cell-mediated immunity -- Infection -- Overview -- Patient-centered collaborative care -- Assessment. Planning and Implementation Community-Based Care -- Pain -- Overview -- Patient-centered collaborative care -- Assessment -- Interventions -- Nonsurgical Management -- Community-Based Care -- Perioperative Care -- Preoperative issues -- Overview -- Patient-centered collaborative care -- Assessment -- Planning and Implementation -- Final Preoperative Preparation -- Intraoperative issues -- Overview -- Patient-centered collaborative care -- Assessment -- Planning and Implementation -- Postoperative issues -- Overview -- Patient-centered collaborative care -- Assessment -- Planning and Implementation -- Nonsurgical Skin Management -- Surgical Management -- Management of Surgical Pain -- Prevent Hypoxemia -- Community-Based Care -- Substance Abuse -- Overview -- Types of dependencies -- Alcohol -- Patient-Centered Collaborative Care -- Assessment -- Interventions -- Nicotine -- Patient-Centered Collaborative Care -- Stimulants -- Hallucinogens and related compounds -- Depressants -- Opioids -- Inhalant abuse -- Steroids -- Part Two: Diseases and Disorders -- Abscess, anorectal -- Abscess, brain -- Overview -- Patient-centered collaborative care -- Abscess, Hepatic -- Abscess, lung -- Abscess, Pancreatic -- Abscess, peritonsillar -- Abscess, Renal -- Acidosis, Metabolic -- Overview -- Patient-centered collaborative care -- Assessment -- Interventions -- Acidosis, Respiratory -- Overview -- Patient-centered collaborative care -- Assessment -- Interventions -- Acute coronary syndromes -- Acute Respiratory Distress Syndrome -- Overview -- Patient-centered collaborative care -- Assessment -- Interventions -- Adrenal Insufficiency (Adrenal Hypofunction) -- Overview -- Patient-centered collaborative care -- Assessment -- Interventions -- Alkalosis, Metabolic -- Overview -- Patient-centered collaborative care -- Assessment -- Interventions -- Alkalosis, Respiratory -- Overview -- Patient-centered collaborative care -- Assessment.
Includes index.
Keywords: NURSING -- HANDBOOKS, MANUALS, ETC